Molecular profiling of signet ring cell colorectal cancer provides a strong rationale for genomic targeted and immune checkpoint inhibitor therapies - Alvi, Muhammad A; Loughrey, Maurice B; Dunne, Philip; McQuaid, Stephen; Turkington, Richard; Fuchs, Marc-Aurel; McGready, Claire; Bingham, Victoria; Pang, Brendan; Moore, Wendy; Maxwell, Perry; Lawler, Mark; et al. (British journal of cancer, 2017)
Background: Signet ring cell colorectal cancer (SRCCa) has a bleak prognosis. Employing molecular pathology techniques we investigated the potential of precision medicine in this disease. Methods: Using test ( n =26) and validation ( n =18) cohorts, analysis of mutations, DNA methylation and transcriptome was carried out. Microsatellite instability (MSI) status was established and immunohistochemistry (IHC) was used to test for adaptive immunity (CD3) and the immune checkpoint PDL1. Results: DNA methylation data split the cohorts into hypermethylated ( n =18, 41%) and hypomethylated groups ( n =26, 59%). The hypermethylated group predominant in the proximal colon was enriched for CpG island methylator phenotype (CIMP), BRAF V600E mutation and MSI ( P <0.001). These cases also had a high CD3 + immune infiltrate ( P <0.001) and expressed PDL1 ( P =0.03 in intra-tumoural lymphoid cells). The hypomethylated group predominant in the distal colon did not show any characteristic molecular features. We also detected a common targetable KIT mutation (c.1621A>C) across both groups. No statistically significant difference in outcome was observed between the two groups. Conclusions: Our data show that SRCCa phenotype comprises two distinct genotypes. The MSI + /CIMP + / BRAF V600E + /CD3 + /PDL1 + hypermethylated genotype is an ideal candidate for immune checkpoint inhibitor therapy. In addition, one fourth of SRCCa cases can potentially be targeted by KIT inhibitors.